San Jacinto 1 : - Oyuela-Caycedo, Augusto (The University of Alabama Press, 2005)
"An outstanding summary of the important San Jacinto site.... Few sites in the Americas offer this kind of window into early human complexity....The authors have written a remarkable synthesis of the ecological and behavioral issues surrounding early pottery making and intensive plant manipulation in the lowland tropics of Colombia. Geographers, anthropologists, botanists, ecologists, Latin Americanists, and archaeologists will find this an essential source of information on a key region of early South American civilization." - Tom D. Dillehay, Vanderbilt University"